2021
DOI: 10.1186/s12886-021-01949-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5-year outcomes between trabeculectomy combined with phacoemulsification and trabeculectomy followed by phacoemulsification: a retrospective cohort study

Abstract: Background We aimed to compare the outcomes of trabeculectomy combined with phacoemulsification and those of trabeculectomy followed by phacoemulsification. Methods A total of 141 patients with primary open-angle glaucoma, exfoliation glaucoma, and glaucoma secondary to uveitis glaucoma who underwent trabeculectomy followed by (n = 48) or combined with (n = 93) phacoemulsification were included. We analyzed data collected from the Collaborative Ble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
9
1
1
Order By: Relevance
“…Since the allocation of cases was made according to the ophthalmologists’ discretion, these differences may indicate that the residents handled the less complex cases. A 5-year follow-up study reported poorer outcomes of trabeculectomy in younger patients 23. In our study, the mean difference of age between groups is ~10 years, which may not be clinically significant.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Since the allocation of cases was made according to the ophthalmologists’ discretion, these differences may indicate that the residents handled the less complex cases. A 5-year follow-up study reported poorer outcomes of trabeculectomy in younger patients 23. In our study, the mean difference of age between groups is ~10 years, which may not be clinically significant.…”
Section: Discussioncontrasting
confidence: 51%
“…A 5-year follow-up study reported poorer outcomes of trabeculectomy in younger patients. 23 In our study, the mean difference of age between groups is ~10 years, which may not be clinically significant. Moreover, it would not explain the worse outcomes in the residents' group.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies support the synchronous combined phacotrabeculectomy, while other surgeons first perform the trabeculectomy and then the phacoemulsification. In fact, no significant differences in the cumulative probabilities of success were found between the two surgical approaches at a 5-year follow-up period [ 21 ]. In our study, we preferred to perform combined phacotrabeculectomy, so as to have the advantage of a single procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Так, Arimura S і сп. (2021) [3] протягом 5-річного спостереження не відмітили різниці в рівні ВОТ у групі комбінованої хірургії трабекулоектомії з ФЕК і в групі, у якій проводили трабекулоектомію з ФЕК у майбутньому.…”
Section: обговоренняunclassified